Prevalence of Helicobacter pylori in children in eastern Turkey and molecular typing of isolates - Ozbey, Gokben; Dogan, Yasar; Demiroren, Kaan; Ozercan, Ibrahim Hanifi (Soc Brasileira Microbiologia, 2015)
The objectives of the present study were to determine Helicobacter pylori via culture, polymerase chain reaction and histopathological diagnosis in 101 children ranging in age from 4 to 18 years, to identify the association among restriction fragment length polymorphism types and clinical disease and to investigate the relationships among different isolates of H. pylori in different age groups. We observed a high prevalence of H. pylori infections in children between the ages of 13 and 18 (75.8%), while children aged 4 to 6 years had the lowest prevalence of infection (40%). H. pylori was detected in 30.7% (31 of 101), 66.3% (67 of 101) and 63.2% (60 of 95) of children as determined by culture methods, PCR and histological examination, respectively. H. pylori isolates with RFLP types I and III were the most common among children with antral nodularity, whereas RFLP types II and IV were the least detected types. Interestingly, all isolates from peptic ulcer patients were type III. Although our results show a high prevalence of H. pylori infections in the pediatric population in eastern Turkey, no association was identified between H. pylori infection with antral nodularity and recurring abdominal pain. In addition, we found low genetic variation among H. pylori isolates from children and no association between RFLP types and antral nodularity (p > 0.05). Additionally, we found that H. pylori isolates with specific RFLP types were predominant in different age groups.
Keywords: children; culture; Helicobacter pylori; PCR-RFLP